2015
DOI: 10.1159/000442208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Immune-Neuroendocrine Biomarker Panel for Detection of Depression: A Joint Effects Statistical Approach

Abstract: Background/Aims: Less than half of depression patients are correctly diagnosed within the primary care setting. Previous proteomic studies have identified numerous immune and neuroendocrine changes in patients. However, few studies have considered the joint effects of biological molecules and their diagnostic potential. Our aim was to develop and validate a diagnostic serum biomarker panel identified through joint effects analysis of multiplex immunoassay profiling data from 1,007 clinical samples. Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The data on the levels of Alpha-2-macroglobulin in mental disorders vary substantially in various publications. The increase in Alpha-2-macroglobulin level in patients with MD was found by [90, 95, 96]. Besides, Alsaif et al [24] and Song et al [22] have found the decrease in patients with BD in comparison with healthy controls.…”
Section: Resultsmentioning
confidence: 84%
“…The data on the levels of Alpha-2-macroglobulin in mental disorders vary substantially in various publications. The increase in Alpha-2-macroglobulin level in patients with MD was found by [90, 95, 96]. Besides, Alsaif et al [24] and Song et al [22] have found the decrease in patients with BD in comparison with healthy controls.…”
Section: Resultsmentioning
confidence: 84%
“…We identified six proteins (represented by six peptides) as biomarkers of MDD: AACT, APOE, APOH, FETUA, HBA and PHLD, which have functional roles in inflammatory response, lipid transport and metabolism, blood coagulation and oxygen transport 44 . Alterations in peripheral proteins involved in inflammatory response, the hypothalamic–pituitary–adrenal (HPA) axis, and carbohydrate and lipid metabolism have been reported in previous biomarker studies on depression 4551 . Other apolipoproteins (apolipoprotein A, apolipoprotein B, apolipoprotein C-III and apolipoprotein D) have also been linked to depression 47,5255 .…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Svenningsson et al (2014) showed that reduction in p11 in PBMCs could potentially predict antidepressant response to citalopram. Additionally, there is growing evidence of multiple dysregulated contributing factors, including growth factors, altered endocrine factors ( Schmidt et al, 2011 ) or immune-related pathways ( Belzeaux et al, 2016 ; Chan et al, 2016b ) in mood disorders and/or in antidepressant responses. Thus, a viable alternative to the single-biomarker approach could be the development of biomarker panels to provide coverage of multiple biological factors that contribute to the heterogeneity of MDD and treatment response ( Schmidt et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%